Experimental Rnomics: The Identification And Characterization Of Small Non-Protein-Coding Rna (Npcrna) In Vibrio Cholerae - Hoe, Chee Hock (2013)
Non-protein-coding RNAs (npcRNAs) are RNA that are not translated into protein but are involved in a myriad of cell regulatory processes including orchestrating bacterial general stress responses and bacterial virulence. The identification and characterization of npcRNAs from the etiologic agent of cholera, Vibrio cholerae (V. cholerae) El Tor, was reported in this study. Using experimental RNomics approaches, 224 npcRNA candidates have been identified; 92 belong to the class of putative cis-antisense npcRNAs, whereas 132 are the intergenic npcRNAs. Among these npcRNA candidates, differential expressions for 56 of them could be verified via Northern blot analysis. Parallelly, 627 npcRNA candidates were reported by another group in a transcriptomic profile survey in V. cholerae El Tor N16961 using RNA-seq. Intriguingly, only 39 npcRNA candidates were common to both datasets. A series of defined tests prompted that RNA substrate, phosphorylation status, C-tailing, adapter ligation, and different sequence of adapter are significant sources of the bias between conventional sequencing and deep sequencing. This suggested that the data in our study is valid and further characterization of the npcRNA candidates was carried out. Two intergenic npcRNA genes were developed as potential diagnostic markers, which could in a multiplex PCR assay serve to be an important tool in molecular epidemiological studies of V. cholerae.